DEVELOPING POCKET BOOK AS LEARNING MEDIA TO TEACH PRONUNCIATION ON SPEAKING SKILLS FOR SEVENTH GRADE STUDENTS IN SMPQ AL-KHUSNA PONGGOK - Muhammad Wildan Kholid; Siti Rofi'ah; Ahmad Saifudin (PROJECT (Professional Journal of English Education), 2023)
This research was carried out based on process and the results of observation at SMPQ Al-Khusna Ponggok. This research was aimed to develop of pocket book to improve speaking skill students. The researcher founded problems in the learning process of the student about the student was difficult of mastering English especially pronunciation. Besides, the student has used conventional book from government and the students was unfamiliar with pronunciation. The subject of the research was carried out by eighteen students of SMPQ Al-Khusna Ponggok. The research method used is R&D method where researcher conducted seven steps. The steps include: need analysis, planning, product development, validation, revision, product trial, and evaluation . The researcher was used seven instruments: (1) need analysis, (2) planning, (3) product development, (4) validation, (5) revision, (6) product trial (7) evaluation. Based on the result was carried out, the results obtained by material was 75%, the media were 93.1% and the student response was 86,6%. The results of the validation of media experts, material experts and student responses can be said that The development media of pocket book to improve speaking skill students of 7th grade SMPQ Al-Khusna Ponggok has feasible level of validity. Keywords:  Pocket Book; Speaking Skill; R&D Method